Cenozoic exhumation patterns in the northern Andes: Constraints from the southern Bucaramanga Fault, Eastern Cordillera, Colombia. (November 2021) - Velandia, Francisco; Bermúdez, Mauricio A.; Kohn, Barry; Bernet, Matthias; Zuluaga, Carlos A.; Brichau, Stephanie
Abstract: The left lateral strike-slip Bucaramanga Fault exhibits a transpressional southern termination located towards the axial zone of the Eastern Cordillera of Colombia, where the Boyacá and Soapaga Faults are also identified as inversion-related structures. To unravel their exhumation history, we obtained apatite and zircon: fission-track and (U–Th)/He ages from samples collected along different structural domains, along five vertical profiles. Joint Bayesian inverse modeling of these data reveals at least four different episodes of cooling. These are: (i) 50 ± 5 Ma, (ii) 20 ± 5 Ma, (iii) 12 ± 3 Ma, and (iv) 5 ± 3 Ma. The earliest pulse is associated with reactivation of the Boyacá and Soapaga Faults. The second pulse is related to the transpressive reactivation along the southern termination of the Bucaramanga Fault and coincides with a marked increase in relief. The Miocene-Pliocene pulses are related to Bucaramanga Fault strike-slip reactivation. Older fission-track ages previously reported from other areas of the Santander Massif suggest migration of exhumation from north to south. The four cooling episodes identified in this study can be related, within a broader geodynamic context, to interaction between the Cocos, Nazca, Caribbean, and South American plates, and the accretion of large tectonic domains of different affinity (oceanic or continental) against the South American plate during the Cenozoic. Our results are consistent with previous work reported in the Santander Massif. The ages observed in the in-situ data correspond with the ages found in modern river sediments and support relief development from the Eocene to the present. Highlights: New thermochronologic data reported for the Eastern Cordillera of Colombia. An exhumation pulse occurred in early Eocene time. Significant cooling at 20 ± 5 Ma defines the onset of fault transpression and a significant increase in relief. Miocene-Pleistocene cooling pulses are related to Bucaramanga Fault reactivation. Exhumation along the Bucaramanga Fault migrated from north to south.